Gender medicine and oncology: report and consensus of an ESMO workshop. (15th October 2019) - Wagner, A D; Oertelt-Prigione, S; Adjei, A; Buclin, T; Cristina, V; Csajka, C; Coukos, G; Dafni, U; Dotto, G -P; Ducreux, M; Fellay, J; Haanen, J; et al.
Abstract: Background: The importance of sex and gender as modulators of disease biology and treatment outcomes is well known in other disciplines of medicine, such as cardiology, but remains an undervalued issue in oncology. Considering the increasing evidence for their relevance, European Society for Medical Oncology decided to address this topic and organized a multidisciplinary workshop in Lausanne, Switzerland, on 30 November and 1 December 2018. Design: Twenty invited faculty members and 40 selected physicians/scientists participated. Relevant content was presented by faculty members on the basis of a literature review conducted by each speaker. Following a moderated consensus session, the final consensus statements are reported here. Results: Clinically relevant sex differences include tumour biology, immune system activity, body composition and drug disposition and effects. The main differences between male and female cells are sex chromosomes and the level of sexual hormones they are exposed to. They influence both local and systemic determinants of carcinogenesis. Their effect on carcinogenesis in non-reproductive organs is largely unknown. Recent evidence also suggests differences in tumour biology and molecular markers. Regarding body composition, the difference in metabolically active, fat-free body mass is one of the most prominent: in a man and a woman of equal weight and height, it accounts for 80% of the man's and 65% of the woman's body mass, and is not taken into account in body-surface area based dosing of chemotherapy. Conclusion: Sex differences in cancer biology and treatment deserve more attention and systematic investigation. Interventional clinical trials evaluating sex-specific dosing regimens are necessary to improve the balance between efficacy and toxicity for drugs with significant pharmacokinetic differences. Especially in diseases or disease subgroups with significant differences in epidemiology or outcomes, men and women with non-sex-related cancers should be considered as biologically distinct groups of patients, for whom specific treatment approaches merit consideration.